Transradial versus tibiopedal access approach for endovascular intervention of superficial femoral artery chronic total occlusion. Issue 7 (18th July 2018) - Patel, Apurva; Parikh, Roosha; Htun, WahWah; Bellavics, Robert; Coppola, John T.; Maw, Myo; Bertrand, Olivier F.; Puma, Joseph A.; Ruzsa, Zoltán; Kwan, Tak W.
Abstract: Background: Improved equipment and techniques have resulted in transition from surgical bypass to endovascular intervention to treat superficial femoral artery (SFA) chronic total occlusions (CTO). A change in access site to radial (TRA) or tibiopedal (TPA) artery for the treatment of these SFA CTO has been reported. The feasibility, efficacy and safety of these two access sites for treatment of SFA CTO have not been reported. Methods: We performed an as treated analysis of 184 SFA CTO interventions in 161 patients from 01/2014 to 09/2016 using either primary TRA or TPA (operator discretion) at two institutions. Primary end point was 30 day major adverse event (MAE) ‐ death, amputation or target vessel revascularization, secondary endpoint was success of procedure. Results: Primary TRA was used in 46 patients with 47 CTO lesions .Primary TPA was used in 115 patients with 137 CTO lesions. Primary crossing success rate was higher with TRA compared to TPA (74% vs 54%, P = 0.01). Dual TRA‐TPA was required in 72 prior uncrossed lesions resulting in a crossing and procedural success of 99% and 96% respectively. The overall crossing and procedural success rate using either of these approaches was 99% and 98% respectively. The 30 day MAE was 5% in TRA arm, 0% in TPA arm and 2% in dual TRA‐TPA arm, P = 0.08. All access sites were patent, confirmed by ultrasound. Conclusion: The treatment of SFA CTO is feasible and safe using both TRA or TPA approach providing high success rates and no access site complications.